Anarquia, beleza e magia : Luís Antonio Martinez Corrêa e O percevejo na cena brasileira - Silva, Cássia Abadia da (2016)
This work shows the loving interdisciplinary relation of history and theater, in which the research object is the brazilian encenation of O percevejo in 1981 in the Dulcina Theater in Rio de Janeiro and The encenation in Sesc Pompeia, in 1983 in São Paulo, under the direction of Luís Antonio Martinez Corrêa (1950-1987). We propose to analyse the text adaption procedure, the (re)lecture, The (re)creation and the (re)appropriation to our stages. The purpose is to comprehend what this project was in the brazilian theater scene. In order to do this we worked with a significant number of research materials in different manners, that include the theater critic, photography, theater programs, adapted scripts, interviews and more.